A comparative study of shear crack growth mechanisms in concrete through acoustic emission analysis - Lian Huang; Junjie Deng; Duo Hu; Xiaolong Li; Yun Liu; Weihua Zhu (Scientific Reports)
Abstract The shear failure of concrete is a sudden brittle failure, which is difficult to be forewarned. To investigate the shear crack mechanisms in concrete, this study first systematic compared acoustic emission (AE) behavior during direct shear tests, compression shear tests (Z-shaped specimens), and three point bending shear tests. AE parameters (amplitude, cumulative count and energy), average frequency (AF)-rise time/amplitude (RA) analysis, K-means clustering, and b-value analysis were integrated to classify cracks and characterize damage progression. The correlation between the shear crack propagation mechanism of concrete and AE parameters was revealed. The AE activity during concrete shear failure was successfully characterized, providing valuable insights into the damage development and evolution processes. The research findings establish a quantitative framework for using AE technology to detect shear cracks and monitor real-time damage evolution in concrete structures.